Resistensi Fraktur pada Mahkota Gigi Tiruan Cekat Berbahan Zirkonia : Literature Review (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Introduction:All-zirconia crowns are the strongest ceramic artificial crowns, made from zirconium, a silicate compound (ZrSiO4) and resistant to high temperatures. The advantages of zirconia include good mechanical properties, biocompatibility, and high corrosion resistance. Zirconia has disadvantages, such as a lack of aesthetic similarity to natural teeth. Methods and Results: Search for published articles on Elsevier, PubMed and Science Direct using predetermined keywords, namely crown,fracture resistance, and zirconiaThis literature review utilizes literature published between 2020 and 2025, accessible in full-text PDF format. Based on data searches using predetermined keywords, data was searched for the last five years, resulting in four selected articles. Discussion: Fracture and loss of retention are problems that can occur in zirconia crowns. Several factors influence the fracture resistance of clinical crowns, such as the load received, the preparation results, material thickness, cement used, marginal adaptation and the zirconia content used. Conclusion: Zirconia crowns are the strongest ceramic artificial crowns. Fracture and loss of retention are problems that can occur in zirconia crowns. Several factors influence the fracture resistance of clinical crowns, such as the load received, the preparation results, marginal adaptation and the zirconia content used.